2011
DOI: 10.1007/s12149-011-0480-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reference tissue modelling for [11C]flumazenil positron emission tomography following head injury

Abstract: These results indicate that reference tissue modelling with the pons as the reference region is valid for [(11)C]FMZ PET in head-injured patients at 6 months following injury within both normal appearing and peri-lesional brain regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…The pons, a part of the brainstem, is known as a region where mGluR1 concentration is negligible, 8 and it is often used as a reference region in noninvasive quantitative PET analysis of neuroreceptors. 29,30 To estimate BP ND for mGluR1 noninvasively with [ 11 C]ITDM-PET, we validated the reference tissue method using the tTAC of the pons. In PET studies with SD rats, accumulation of receptor-bound radioactivity was not observed in the pons (Figures 1 and 2), and there was no significant difference in V T value of the pons between PET studies on animals pretreated with and without FITM for the saturation of mGluR1 binding sites (data not shown), suggesting that the pons is a reasonable reference region.…”
Section: Discussionmentioning
confidence: 99%
“…The pons, a part of the brainstem, is known as a region where mGluR1 concentration is negligible, 8 and it is often used as a reference region in noninvasive quantitative PET analysis of neuroreceptors. 29,30 To estimate BP ND for mGluR1 noninvasively with [ 11 C]ITDM-PET, we validated the reference tissue method using the tTAC of the pons. In PET studies with SD rats, accumulation of receptor-bound radioactivity was not observed in the pons (Figures 1 and 2), and there was no significant difference in V T value of the pons between PET studies on animals pretreated with and without FITM for the saturation of mGluR1 binding sites (data not shown), suggesting that the pons is a reasonable reference region.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, flumazenil displays comparable levels of binding to the GABA A receptors containing α1, α2, α3, or α5 subunits, which is why this compound is considered to be not subtype-selective [ 4 ]. For these reasons, [ 11 C]flumazenil can be considered a versatile PET tracer and it has been used in the study and assessment of several conditions, such as neuronal damage in head injury [ 5 ], epilepsy [ 6 ], stroke-induced penumbral areas of infarction [ 7 ], and Alzheimer’s disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In that context, the quantification of [ 11 C]flumazenil binding has been previously performed by different pharmacokinetic models. In human studies, the one-tissue compartment model (1TCM) and the simplified reference tissue model (SRTM) [ 10 ] using the pons as a reference tissue have been validated [ 11 ] and applied [ 12 14 ]. Although useful, these models have been mostly applied for regional quantification of [ 11 C]flumazenil binding, analyzing the average kinetic profile of a specific volume of interest (VOI).…”
Section: Introductionmentioning
confidence: 99%